2017
DOI: 10.5713/ajas.16.0867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proteinate complex zinc on growth performance, hepatic and splenic trace elements concentrations, antioxidative function and immune functions in weaned piglets

Abstract: ObjectiveTo assess the effects of proteinate complex zinc (PC-Zn) on growth performance, antioxidative function, trace element concentrations and immune function in weaned piglets.MethodsThree hundred newly weaned barrows (Duroc×Landrace×Yorkshire), 28 days of age, were randomly allotted to 3 dietary groups of 5 replicate pens per group for 4 weeks of feeding. Experimental diets were: i) zinc deficient diet (ZnD, 24 mg/kg Zn supplementation from ZnSO4), ii) inorganic Zn diet supplemented with 120 mg/kg of Zn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…In the current study, SOD activity throughout the week 0 trailer stressor tended to be higher for INORG than CTM horses, whereas GPx activity was higher for CTM than INORG horses in both muscle groups at all sampling times. These results are in contrast to previously published literature in food animals showing an increase in SOD activity in various organs following complexed trace mineral supplementation 4 , 5 . A similar inverse relationship between SOD and GPx expression and activity has been shown in horses supplemented with dietary antioxidants 14 , 15 , which has been suggested to indicate a preference for use of the GPx over the SOD antioxidant system in horses with more favorable antioxidant or selenium (Se) status.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the current study, SOD activity throughout the week 0 trailer stressor tended to be higher for INORG than CTM horses, whereas GPx activity was higher for CTM than INORG horses in both muscle groups at all sampling times. These results are in contrast to previously published literature in food animals showing an increase in SOD activity in various organs following complexed trace mineral supplementation 4 , 5 . A similar inverse relationship between SOD and GPx expression and activity has been shown in horses supplemented with dietary antioxidants 14 , 15 , which has been suggested to indicate a preference for use of the GPx over the SOD antioxidant system in horses with more favorable antioxidant or selenium (Se) status.…”
Section: Discussioncontrasting
confidence: 99%
“…Dietary complexed trace mineral supplementation has been shown to reduce oxidative stress in food animal models 1 3 . Dietary proteinate complexed-Zn supplementation increased glutathione peroxidase ( GPx ) and superoxide dismutase ( SOD ) activities in the spleen of barrows 4 . Additionally, biocomplexed minerals Fe, Mn, Zn, and Cu enhanced SOD and GPx activities in the liver of grower-finisher pigs 5 and decreased plasma malondialdehyde ( MDA ), a measure of oxidative stress, in broilers 1 .…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, Zn deficiency in rats gave rise to an increase in oxidative stress and DNA damage, and this was alleviated by a dietary supplemented Zn [ 30 ]. It has also been demonstrated that piglets fed the diet supplemented with organic Zn-chelate exhibited a greater deposition of Zn and levels of SOD, GPX, and metalothonemin compared with those fed the diet supplemented with inorganic ZnO [ 31 ]. Therefore, the beneficial effects of supplemental Zn on the extent of antioxidant capacity should be associated with its bioavailability to cope with reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Weaned pigs fed 500 ppm of nano ZnO had reduced serum malondialdehyde concentrations, increased serum glutathione peroxidase activity, and increased Nrf2 gene expression in the jejunum compared with those fed basal diets [ 31 ]. Compared with Zn-deficient pigs, pigs fed 120 ppm of Zn from Zn proteinate increased the activities of superoxide dismutase and glutathione peroxidase in the spleen and liver [ 32 ]. Results from these studies show the importance of adequate Zn supplementation to support its role in antioxidant functions and alleviating cell damage induced by oxidative stress.…”
Section: Essentiality Of Zincmentioning
confidence: 99%